Answer:
I believe it is 3.75
Step-by-step explanation:
(5^49/5^48)+4^0−(1)^79⋅(−3/−4^9)^0
5+1−(1)^79⋅(−3/−4^9)^0
5+1−(1)^79
5⋅(−3/−4^9)^0
-3 divided by -4 to the power of 9 to the power of 0=0.75
5 times 0.75=3.75
Hope this is correct! xx
Answer:5
Step-by-step explanation:
3^2+4^2=c^2
9+16=c^2
25=c^2
=c
5=c
Answer:
2/11
Step-by-step explanation:
6 = 2 x 3
6/11 x 1/3
= ( 6 x 1 )/( 11 x 3 )
= ( 2 x 3 x 1 )/( 11 x 3 )
Cancel 3 in both numerator and denominator.
= ( 2 x 1 )/( 11 )
= 2/11
Answer: x = - 7/12
Step-by-step explanation:
-3x + 2 - 5x - 7 = 4x + 2
=> -8x - 5 = 4x + 2
=> -12x = 7
=> x = - 7/12
Answer:
C) 3/8
Step-by-step explanation:
Find 1/8 + 1/4
1/8 + 1/4
= 1/8 + 2/8
= 3/8